Comunicação banal e quotidiano em um mercado de Belém - CASTRO, Marina Ramos Neves de (Associação Nacional dos Programas de Pós-Graduação em Comunicação, 2022)
This article describes an ethnographic research carried out at the Guamá fair, in Belém (PA), during the years 2011 to 2018. The objective was to understand the communicational and cultural processes present in the social interactions of this fair, thus trying to describe the typifications that make up the intersubjectivity of the social subjects who attend it. In this way, these typifications are described and discussed as the social form of a banal everyday life and an attempt is made to think about these typifications through the Heideggerian notion of chatter (Gerede), understood as a communicational-cultural process affected by the banality of everyday life.